2022
DOI: 10.1002/pmrj.12801
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided percutaneous carpal tunnel release: A systematic review

Abstract: Objective Carpal tunnel syndrome (CTS) is the most common peripheral entrapment mononeuropathy. The purpose of this systematic review is to evaluate the reported clinical effectiveness and safety of ultrasound‐guided percutaneous carpal tunnel release (USCTR) for the treatment of CTS. Literature Survey PubMed, EMBASE, and ScienceDirect databases were queried from database inception to February 20, 2021, to identify clinical studies on USCTR. Methodology Two reviewers independently completed title, abstract, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Previous studies have reported that TCTR provides better outcomes, faster recovery, and quicker return to work than open CTR or endoscopic CTR [13,14,15,16]. Most patients experienced a reduction in pain within 12 h after TCTR.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have reported that TCTR provides better outcomes, faster recovery, and quicker return to work than open CTR or endoscopic CTR [13,14,15,16]. Most patients experienced a reduction in pain within 12 h after TCTR.…”
Section: Discussionmentioning
confidence: 85%
“…CTR-US represents an increasingly popular treatment for CTS [ 25 ], which may be able to provide the benefits of ECTR while avoiding the limitations of ECTR such as a reduced field of view [ 26 ]. Although CTR-US was first described as early as 1997 [ 27 ], recent advances in the quality, availability, and affordability of ultrasound technology have allowed this technique to become more commonly studied [ 6 , 25 ]. The primary advantage of CTR-US is the ability of the provider to identify all relevant anatomical landmarks despite being a minimally invasive technique [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…Variable rates of revision surgical procedures have been reported, ranging from less than 1% to 12% [ 4 ]; most studies report revision rates between 0.5% and 1.5% [ 5 ]. While traditional open CTR is the most common surgical technique used to treat CTS, newer techniques, such as carpal tunnel release using real-time ultrasound guidance (CTR-US), may offer some advantages with accelerated recovery in the postoperative period [ 6 ]. As with any new technique, some potential adopters may have questions pertaining to the learning curve of the procedure [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of interventional procedures using high-frequency ultrasound, ultrasound-guided percutaneous carpal tunnel release (USCTR) using various dividing instruments was proposed to overcome these limitations of OCTR and ECTR [ 6 ]. Among the USCTR, the thread carpal tunnel release (TCTR) was first proposed by Danqing Guo and his colleagues [ 7 ], which can transect the TCL without skin incision, leaving only two needle punctures [ 8 ].…”
Section: Introductionmentioning
confidence: 99%